2013
DOI: 10.1038/srep01215
|View full text |Cite
|
Sign up to set email alerts
|

Robust shifts in S100a9 expression with aging: A novel mechanism for chronic inflammation

Abstract: The S100a8 and S100a9 genes encode a pro-inflammatory protein (calgranulin) that has been implicated in multiple diseases. However, involvement of S100a8/a9 in the basic mechanisms of intrinsic aging has not been established. In this study, we show that shifts in the abundance of S100a8 and S100a9 mRNA are a robust feature of aging in mammalian tissues, involving a range of cell types including the central nervous system. To identify transcription factors that control S100a9 expression, we performed a large-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
123
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(131 citation statements)
references
References 65 publications
(116 reference statements)
3
123
1
Order By: Relevance
“…In addition, S100a8/a9 may act as leukocyte chemo-attractants (29) and induce the expression of pro-inflammatory cytokines (30), causing a positive feedback in inflammation. In aged mice and humans, increases in the mRNA levels of S100a8 and S100a9 have been demonstrated in multiple tissues including the central nervous system (31). Recently, S100a9 (calgranulin B), an important pro-inflammatory mediator in acute and chronic inflammation (3234), was identified as a contributor to amyloid plaque accumulation (35).…”
Section: 4 Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, S100a8/a9 may act as leukocyte chemo-attractants (29) and induce the expression of pro-inflammatory cytokines (30), causing a positive feedback in inflammation. In aged mice and humans, increases in the mRNA levels of S100a8 and S100a9 have been demonstrated in multiple tissues including the central nervous system (31). Recently, S100a9 (calgranulin B), an important pro-inflammatory mediator in acute and chronic inflammation (3234), was identified as a contributor to amyloid plaque accumulation (35).…”
Section: 4 Discussionmentioning
confidence: 99%
“…These findings are consistent with our observation of increased expression of neuronal and axonal survival genes in aerobic but not in stretch exercise training. Recently, Swindell and colleagues showed significantly increased expression of S100 genes in both blood and the hippocampus of aging human tissues (31), suggesting that molecular aspects of the underlying pathology may have a systemic component, making blood cell-derived data relevant. These observations are consistent with existing evidence arguing that exercise adaptation can decrease the levels of pro-inflammatory cytokines (46, 47).…”
Section: 4 Discussionmentioning
confidence: 99%
“…74 To identify transcription factor binding sites enriched in 1 kb sequences upstream of differentially expressed genes, we used semiparametric generalized additive logistic models (GAM). 75 For all human genes, we scanned upstream regions for matches to a set of 1937 position weight matrix (PWM) motifs, which represent the empirically-determined binding affinities of known human transcription factors and unconventional DNA-binding proteins. Methods used to aggregate and filter the complete set of 1937 motifs have been described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, S100A8/9 have been shown to be overexpressed during aging, which triggers a forward feed cycle which results in a sustained pro-inflammatory environment which increases with age (Swindell et al, 2013). In addition, a recent study demonstrated that S100A9 is released from influenza infected cells and can act as a DAMP to enhance inflammatory responses and viral pathogenesis during influenza virus infection (Tsai et al, 2014).…”
Section: S100 Proteinsmentioning
confidence: 99%
“…S100A8 and S100A9 are EF-hand Ca 2+ binding proteins which belong to the family of low molecular weight S100 proteins (10-13 kDa) consists of 22 members (Ravasi et al, 2004;Yan et al, 2008). The genes of S100A8 and A9 encode a pro-inflammatory protein known as calgranulin (Swindell et al, 2013). Most of S100 proteins share conserved structural motifs of two EF-hand Ca 2+ -binding domains connected by a variable hinge region that often confer biological activity (Yan et al, 2008).…”
Section: S100 Proteinsmentioning
confidence: 99%